A Strategy to Prevent Radicalism at Integrated of Islamic Elementary School Students : (Case study on integrated Islamic elementary school students in the city of Padang) - Adriantoni Adriantoni; Zulfahman Siregar; Nursyamsi Nursyamsi (STAI Syaichona Moh. Cholil Bangkalan, 2022)
The purpose of this study was to determine the school's strategy for preventing radicalism in integrated Islamic elementary schools. The type of research used was qualitative with data collection techniques of observation, interviews and documentation, then analyzed the data by reduction. The results of this study indicate, first: The integration of the Integrated Islamic Elementary School learning curriculum in the city of Padang is divided into four types, namely strengthening the curriculum that applies to strengthening character, and strengthening students' personal in order to face global challenges. Second, the strategy in extracurricular activities is carried out in a structured and systematic pattern. The three environmental creation strategies are pursued in an Islamic atmosphere, non-discriminatory, based on genetic characteristics, upholding ethical values, respecting cultural pluralism, and being polite to school members. The four strategies for routine, spontaneous and exemplary activities in an effort to prevent radicalism are carried out by strengthening character, combining learning activities, nurturing and habituation in the form of worship activities, order, neatness and cleanliness, eating and drinking, and social behaviour.